DEVELOPMENT OF METHODOLOGICAL APPROACHES TO OBTAINING ISLET CELLS BASED ON THE RESULTS OF THE MORPHOLOGICAL ANALYSIS OF THE PANCREAS OF RABBITS OF DIFFERENT AGES - N. N. Skaletskiy (Vestnik Transplantologii i Iskusstvennyh Organov, 2014)
Purpose. A comparative morphological analysis of adult pancreas and newborn rabbits as acceptable model for obtaining of islet cell cultures having a low immunogenicity was agoal of this study. Materials and methods. Pancreas from adult and newborn rabbits and islet cell culture was examined by histological and immunohistochemical techniques. Results. Shown, the pancreas of adult rabbits contains great amount of exocrine tissue and culturing it does not allow to obtain the purified islets of impurities. By contrast, pancreas of newborn rabbits in which the ratio of the islets and the exocrine tissue is much higher, it is possible to obtain highly purified cultures of islet cells. Conclusion. Morphological features of newborn rabbit pancreas can use it as a model for obtaining cultures of islet cells having low immunogenicity.